Effect of study habits counselling on senior students' achievement in English language - Dekera G. Atim; Comfort M. Maor; Rejoice Atim; Nancy N. Igyu (Northern Negros State College of Science and Technology (NONESCOST), 2022)
This study investigated the effect of study habits counselling on the academic achievement of senior secondary school students achievement in English language in North-west, Benue State, Nigeria. The study adopted a Quasi-experimental design. The population of the study was five thousand, three hundred and twenty nine SS2 students (5,329) of public schools. The sample size for the study was 100 senior secondary school 2 students drawn from intact class of a public school through multi stage sampling technique. Two instruments were used for the collection of data, English Achievement Test (EAT) and Study Habits Counselling Questionnaire (SHCQ). The reliability of the research instruments was established using Lemma co-efficient Alpha. Data was collected and analyzed using mean and standard deviation to answer research questions and Analysis of Covariance (ANCOVA) to test the hypotheses. Findings revealed that study habits counselling has significant effect on the academic achievement of secondary school students in English. Study habits counselling has no statistical significant difference in the mean score of male and female students. The study concludes that study habits counselling has effect on the academic achievement of students in English, however, there is no significant difference between male and female. Thus, group guidance should be organized in schools to create awareness on effective study habits. A functional school library should be mounted. Parents and guardians should encourage their children to set up schedules for study. Qualified English teachers should be employed in all secondary schools. Guidance counsellors should include study habits counselling as part of new students' orientation to facilitate effective study habits among new students.